RESILIENSI PADA PASIEN HEMODIALISIS: STUDI LITERATUR - Antari, Gusti Ayu Ary (Coping: Community of Publishing in Nursing; Vol 10 No 6 (2022): Desember 2022, 2022)
Resilience is a factor that is closely related to the quality of life and well-being of hemodialysis patients. Resilience acts as a protective factor that plays a role in increasing patient adaptation and skills in carrying out positive coping strategies. Research on resilience in hemodialysis patients is still developing, and it is not yet clear about the factors that can affect resilience in hemodialysis patients. This study aims to determine the factors associated with resilience in hemodialysis patients. The design used is a systematic literature review, where a literature search is carried out through several databases such as PubMed, Science Direct, and ProQuest. A total of five articles are discussed in this study. The results of the analysis show that the level of resilience in hemodialysis patients is still in the low to moderate range. Socio-demographic factors, factors related to hemodialysis conditions, spiritual well-being, family resilience, social support, stress, self-esteem, and depression were found to be related to resilience. The conclusion of this study is that socio-demographic and psychosocial factors can be considered in developing strategies to increase resilience in hemodialysis patients. Improving resilience must be a focus in the care of hemodialysis patients so as to support the achievement of a better quality of life.